The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1503/cjs.031313
|View full text |Cite
|
Sign up to set email alerts
|

Inconsistencies between navigation data and radiographs in total knee arthroplasty are system-dependent and affect coronal alignment

Abstract: Background: Few studies have compared the effect of different computer navigation systems on postoperative alignment in patients who have had total knee arthroplasty (TKA). We examined 2 computed tomography (CT)-free computer navigation systems by comparing the accuracy of intraoperative measurements to postoperative alignment. Methods:Patients underwent unilateral TKA performed by a single surgeon using 1 of 2 CT-free navigation systems. We compared final intraoperative tibial and femoral coronal angles and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The current study used a single infrared-based imageless navigation system to measure coronal mechanical alignment. Although reliable and reproducible, alignment measurements can vary between imageless and computed tomography-based navigation systems 12) and hence the findings of the current study need to be validated using different navigation systems. To the best of our knowledge, this is the first study in the literature which has analysed the effect of sagittal knee deformity on coronal mechanical alignment measurements using preoperative radiographs and navigation during TKA.…”
Section: Discussionmentioning
confidence: 99%
“…The current study used a single infrared-based imageless navigation system to measure coronal mechanical alignment. Although reliable and reproducible, alignment measurements can vary between imageless and computed tomography-based navigation systems 12) and hence the findings of the current study need to be validated using different navigation systems. To the best of our knowledge, this is the first study in the literature which has analysed the effect of sagittal knee deformity on coronal mechanical alignment measurements using preoperative radiographs and navigation during TKA.…”
Section: Discussionmentioning
confidence: 99%
“…In a study performed by Carli et al [ 31 ] comparing two different computer navigation systems, the results showed a significant difference. However, in both study groups there were rather high numbers of outliers, 24 and 32%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing computer navigation systems in orthopedics is not uncommon; yet, most are not related to spine surgeries. 12 , 13 Honl et al compared acetabular cup orientation between five different computer-assisted navigation systems for total hip arthroplasty and demonstrated significant differences among them. 12 In addition, Carli et al compared the accuracy of intraoperative measurements to postoperative tibial and femoral alignment in two different computer-assisted systems for total knee arthroplasty and found a significant difference in the outcome as well.…”
Section: Discussionmentioning
confidence: 99%
“… 12 In addition, Carli et al compared the accuracy of intraoperative measurements to postoperative tibial and femoral alignment in two different computer-assisted systems for total knee arthroplasty and found a significant difference in the outcome as well. 13 Interestingly, several clinical studies have demonstrated high accuracy rates of pedicle screw placement using CT-based navigation compared with other methods, such as freehand technique and fluoroscopic navigation. 14 , 15 However, a critical aspect of the operative procedure was not taken into account, which is the type of computer navigation system being used.…”
Section: Discussionmentioning
confidence: 99%